2021
DOI: 10.3389/fphar.2020.618065
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cells and Their Contribution to the Mechanisms of Action of Cannabidiol in Neuropsychiatric Disorders

Abstract: Cannabidiol (CBD) is a phytocannabinoid with a broad-range of therapeutic potential in several conditions, including neurological (epilepsy, neurodegenerative diseases, traumatic and ischemic brain injuries) and psychiatric disorders (schizophrenia, addiction, major depressive disorder, and anxiety). The pharmacological mechanisms responsible for these effects are still unclear, and more than 60 potential molecular targets have been described. Regarding neuropsychiatric disorders, most studies investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 318 publications
(192 reference statements)
0
9
0
2
Order By: Relevance
“…CBD may operate through components of the endocannabinoid system with low affinity for CB1 and CB2 receptors [ 39 ] or on different neurotransmitter systems and pathways. Other CBD effects may be mediated by direct activation of 5-hydroxytrypamine 1A (5-HT1A) receptors [ 34 , 35 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and peroxisome proliferator-activated receptorγ (PPARγ) [ 17 , 34 ]. In addition, CBD is shown to have an antagonistic effect against THC [ 35 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD may operate through components of the endocannabinoid system with low affinity for CB1 and CB2 receptors [ 39 ] or on different neurotransmitter systems and pathways. Other CBD effects may be mediated by direct activation of 5-hydroxytrypamine 1A (5-HT1A) receptors [ 34 , 35 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and peroxisome proliferator-activated receptorγ (PPARγ) [ 17 , 34 ]. In addition, CBD is shown to have an antagonistic effect against THC [ 35 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among all the above-highlighted mechanisms, the 5-HT1A receptor seems to be the most strongly implicated in the regulatory effects of CBD on mood and mental diseases [ 40 ]. Several pharmacological approaches with selective receptor antagonists such as WAY-100635 showed that anxiolytic-, antidepressant-, and antipsychotic-like effects of CBD are predominantly mediated by 5-HT1A-Rs [ 41 , 42 , 43 ]. 5-HT1A is a crucial serotonergic receptor subtype involved in many functions of serotonin in the brain, and several works have associated many beneficial actions of CBD to this receptor, in accordance with our results [ 34 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, inhibiting CB2Rs with the antagonist AM630 would prevent the antipsychotic effects of M4 agonists. Preclinical studies also showed that cannabidiol (CBD), another major phytocannabinoid, which is devoid of intoxicating effects, has antipsychotic properties [92][93][94][95] mediated by the activation of CB2Rs [96][97][98]. It should be pointed out that CBD is a non-intoxicating rather than a non-psychoactive constituent in the cannabis plant.…”
Section: Schizophrenia and Cb2r-ecsmentioning
confidence: 99%
“…The reports on cannabinoid receptor distribution, signaling and function in oligodendrocytes are still scarce, but several revisions have pointed out the relevance of the endocannabinoid system in oligodendrocyte biology (Haspula & Clark, 2020; Ilyasov et al, 2018; Marinelli et al, 2016; Scarante et al, 2021). Thus, the present review intends to gather and discuss the current knowledge on the presence of cannabinoid receptors in oligodendroglial cells and on how cannabinoids/endocannabinoids affect their function both in cell culture and in vivo.…”
Section: Introductionmentioning
confidence: 99%